The Maternal Donor of Chrysanthemum Cultivars Revealed by Comparative Analysis of the Chloroplast Genome - Xu, Yufen; Liao, Borong; Ostevik, Kate L.; Zhou, Hougao; Wang, Fenglan; Wang, Baosheng; Xia, Hanhan (Frontiers in Plant Science, 2022)
Chrysanthemum (Chrysanthemum morifolium Ramat) is an important floricultural crop and medicinal herb. Modern chrysanthemum cultivars have complex genetic backgrounds because of multiple cycles of hybridization, polyploidization and prolonged cultivation. Understanding the genetic background and hybrid origin of modern chrysanthemum cultivars can provide pivotal information for chrysanthemum genetic improvement and breeding. By now, the origin of cultivated chrysanthemums remains unclear. In this study, 36 common chrysanthemum cultivars from across the world and multiple wild relatives were studied to identify the maternal donor of modern chrysanthemum. Chloroplast (cp) genomes of chrysanthemum cultivars were assembled and compared with those of the wild relatives. The structure of cp genomes was highly conserved among cultivars and wild relatives. Phylogenetic analyses based on the assembled cp genomes showed that all chrysanthemum cultivars grouped together and shared 64 substitutions that were distinct from those of their wild relatives. These results indicated that a diverged lineage of the genus Chrysanthemum, which was most likely an extinct or un-sampled species/population, provided a maternal source for modern cultivars. These findings provide important insights into the origin of chrysanthemum cultivars, and a source of valuable genetic markers for chrysanthemum breeding programs.